Hubungan Pengetahuan, Sikap dan Perilaku Bidan Desa terhadap Kanker Leher Rahim dan Pencegahannya di Kabupaten Sragen - Sutresno, Ismail Joko; Emilia, Ova; Prawitasari, Shinta (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: Cervical cancer (cervix) is the second most common type of cancer in women, with an estimated of 530,000 new cases and more than 270,000 deaths each year. In 2012, cervical cancer cases in Central Java was 2,259 cases. Cervical cancer is easily recognizable and can be prevented with screening. A village midwife as the closest healthcare provider to the community is expected to function better in encouraging the prevention of cervical cancer.if they receive appropriate knowledge and attitude toward screening.Objective: to understand the correlation of knowledge, attitude and behavior of village midwife against cervical cancer and its prevention in Sragen district.Method: This analytic study is using quantitative and qualitative approach. Quantitative studies was done with cross-sectional study. The population of this research were 208 village midwifes from 20 sub-districts in Sragen and the subjects were 118 midwives whom randomly sampled. Data were analyzed using univariate and bivariate analysis.The qualitative study was done using depth interview.Result and Discussion: There is no correlation between age, level of education as well as work duration with their knowledge about cervical cancer prevention (P = 0.787; 0.344; 0.822); there is no correlation between village midwives’ knowledge with their behavior towards cervical cancer prevention (P = 0.664); there is no correlation between the village midwives’ attitudes and behavior towards prevention of cervical cancer (P = 0.460). Qualitative results support the quantitative results.Conclusion: There is no correlation between village midwives’ knowledge, attitudes and behavior towards cervical cancer prevention.Keywords: Cervical cancer, knowledge, attitude, behavior